Concurrent validity of the inertial measurement unit Vmaxpro in vertical jump estimation - Jimenez-Olmedo, J. M.; Pueo, B.; Mossi, J. M.; Villalon-Gasch, L. (Applied Sciences, 2023)
The aim of this study was to evaluate if the inertial measurement unit (IMU) Vmaxpro is a valid device to estimate vertical jump height (VJH) when compared to a motion capture system (MoCAP). Thirteen highly trained female volleyball players participated in this study which consisted of three sessions. After a familiarization session, two sessions comprised a warm-up followed by ten countermovement jumps, resting two min between each attempt. Jump height was measured simultaneously by Vmaxpro using take-off velocity and MoCAP using center-of-mass vertical excursion. Results show significant differences in jump height between devices (10.52 cm; p < 0.001; ES = 0.9), a very strong Spearman`s correlation (rs = 0.84: p < 0.001), and a weak concordance correlation coefficient (CCC = 0.22; p = 0.861; Cb = 0.26). Regression analysis reveals very high correlations, high systematic error (8.46 cm), and a nonproportional random error (SEE = 1.67 cm). Bland-Altman plots show systematic error (10.6 cm) with 97.3 % of the data being within the LoA. In conclusion, Vmaxpro can be considered a valid device for the estimation of VJH, being a cheaper, portable, and manageable alternative to MoCAP. However, the magnitude of systematic error discourages its use where indistinguishable data from Vmaxpro and MoCAP are used unless the corresponding specific fitting equation is applied.